Quantifying seed uniformity and yield advantage of precision planter technologies through use of field tests and machine data - Mishler, Braden D. (Kansas State University, 2021)
In recent years, technologies in the agricultural industry have gotten increasingly advanced. In past decades, most of the machines utilized by farmers were almost entirely mechanical with only a few electronics and computers, if any. Today these mechanically operated machines are increasingly being replaced by highly automated computer-controlled systems. One sector of agricultural equipment where this is especially apparent is precision planters for row crops. In recent years, these machines have gone from ground driven mechanical systems with spring downforce to electrically driven meters utilizing individual row hydraulicly controlled downforce. This research was conducted to examine some of the purported benefits of these newer technologies found on modern planters. The initial investigation of the planter technologies was on the utilization of turn compensation when using electrically driven seed meters. Turn compensation refers to the ability of a planter to adjust seed and fertilizer application rates across the toolbar in order to account for the speed differential caused by planting around a turn or curvilinear pass. In the past, significant research has been conducted on the accuracy of turn compensation utilized by electric driven seed meters, though no existing research could be found on the amount of ground covered in an average field when the technology is being utilized. This research examined a sample of fields with various sizes and shapes to determine the amount of area planted in a typical field where turn compensation is active. In addition to turn compensation, we also conducted research on the advanced hydraulic downforce systems utilized by many of the modern planters. This research was split into two different parts, one looking at the difference between a fixed downforce system and an active downforce system and another part looking at the effect of downforce setting and operation speed choices across two different planting systems. To examine the difference between fixed downforce, which always applies a constant hydraulic pressure, and active downforce, which constantly adjusts the hydraulic pressure to maintain a target downforce, plots were planted at two different locations. For this study plots were planted side by side with each type of downforce to examine the effect on plant spacing, emergence, and ultimately yield. In addition to this research one location was also planted at three different speeds and two different levels of active downforce with two different planter systems. This planting was done to determine the ideal combination of planter downforce and speed that should be utilized for each system to achieve the best combination of seed spacing, depth, emergence, and ultimately yield for each planter system. All of these studies have provided useful insight into the value of these new planter technologies. To continue this research in the future I would recommend that additional investigation be conducted on the turn compensation with a larger toolbar planter. Additionally, I would recommend a second year of testing be conducted on the downforce and speed combinations for the two planter systems.
Keywords: Precision planters; Turn compensation; Planter downforce; Spacing; Emergence